Attitudes of mothers towards over the counter antibiotics for their children in Baghdad city - Shawq, Adraa H.; Ajil , Zaid W.; Al-Musawi, Khatam M. (International Journal of Psychosocial Rehabilitation, 2020)
Objectives to evaluate mothers` attitudes toward OTC antibiotics without consultation, and common reasons for this practice Methods A cross- sectional design conducted at primary health care centres in Baghdad city. Sample of (225) mothers were selected to participated in the study. Data were collected from the period of the 15th October 2015 to the 15th May 2016. A constructed questionnaire format was used to evaluate mothers` attitudes containing 20 items. Results the result of the study showed (45.3%) of mothers at 25-34 years, (24.4%) have primary school education, (65.8%) was housewives, (45.7%) have moderate income, (55.1%) use medication without prescription, (46.2%) their source for medication from pharmacists, and (26.7%, 26.2%) their reasons for self medication were mothers experiences and not availability of near health services. The mean score of mothers` attitudes showed mothers with un accepted attitudes toward OTC antibiotics. Conclusion OTC antibiotics practice was accepted in Iraqi population, mothers` showed un accepted attitudes toward this behaviours. Economical status, level of education, and their age showed a significant association with mothers` attitudes. Recommendation Increased parent awareness toward side effects of antibiotics and bacterial resistance by active communication and social media in addition to activated the governmental role about medication control.